Tinjauan Tentang Tingkat Kebugaran Jasmani Mahasiswa di Pusat Kegiatan Mahasiswa Universitas Negeri Padang - Madrid Ramadhan; Muhamad Sazeli Rifki (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2019)
The problem in this study is the number of activities carried out by Student Activity Centers or abbreviated as PKM Padangakan State University tends to make physical activity outside the sport increase and can make a person's fitness decline. The purpose of this study was to see the extent of the physical fitness of PKM students at Padang State University. The type of this study was descriptive. The population in this study were all PKM students who were included in the daily board as many as 200 students. The sampling technique was using a purposive sampling technique. So the number of samples in this study were 30 students. The instrument in this study was run 2400 or 2.4 K (copper test). The data analysis technique in this study used a descriptive descriptive analysis technique. 1) The results of the study showed that the physical fitness level of male students of PKM Padang State University was in the less category. 2) The level of physical fitness of PKM Padang University female students is very low in category.